Thermal Comfort in Indonesian Vernacular Houses - Sahabuddin Latif; Ashari Abdullah; Siti Fuadillah Alhumairah Amin; Rohana Abdullah; Muhammad Risman (Universitas Muhammadiyah Surakarta, 2026)
Thermal comfort in Indonesian housing is increasingly challenged by hot-humid climates, urban densification, material changes, and rising cooling demand. This study employed a narrative literature review with thematic synthesis. Literature was identified through a Scopus search conducted on 10 May 2026 using thermal-comfort and vernacular-architecture keywords, then supplemented by Indonesian case studies, classic comfort theories, thermal-comfort standards, and policy reports. The selected sources were screened based on relevance to thermal comfort, vernacular or naturally ventilated dwellings, and architectural design, and were appraised according to evidence type, including field measurements, occupant surveys, simulations, reviews, and architectural interpretations. A total of 45 cited sources formed the basis of the thematic synthesis. The review finds that Indonesian vernacular houses do not provide automatic comfort; their performance depends on climate exposure, material integrity, ventilation potential, roof design, shaded transition spaces, and occupant control. Evidence from Acehnese, Banjar, Minangkabau, Bugis, Javanese, Balinese, Palembang, and East Nusa Tenggara houses indicates recurring mechanisms: raised floors, ventilated roof voids, porous but shaded envelopes, semi-outdoor spaces, and climate-specific materials. The article proposes a performance-based translation framework for contemporary low-energy housing. Vernacular principles are most useful when evaluated through measured air movement, radiant heat, humidity, occupant votes, and future climate resilience.